Recalibrating Stance of Survival for Philippine Schools Overseas (PSOs) Amidst Pandemic and Beyond (International Journal of Scientific Research and Management (IJSRM), 2022)
The Covid-19 pandemic has brought disruption in the educational system across the globe. The sudden occurrence of the unprecedented event has resulted to educational crisis that placed the education sector to a position of creating immediate solution to address the changing landscape of learning delivery and continuity. This qualitative inquiry explored the challenges in teaching and learning continuity of Philippine Schools Overseas (PSOs) as a result of the Covid-19 pandemic. In-depth Interviews (IDIs) were conducted from respondents, composed of teachers and school administrators of PSOs from Saudi Arabia, Qatar, Greece, Libya, and East Timor. Using the qualitative data analysis framework, essential themes related to surviving the stance of pandemic were identified, namely: learning continuity amid pandemic, technology supported learning, and the need to provide support to teachers. The need to address learning continuity and develop plans for future directions beyond pandemic was also explored. To ensure teaching and learning continuity amid pandemic and beyond, PSOs need to implement post-pandemic educational model through the development of standards for online learning that articulates maximization of the use of technology that is reflective, sensitive, and responsive in times of crisis and to the needs of the future.